The Principle of Justice in Islamic and Civil Inheritance Law: Legal Disparities, Dispute Resolution, and Harmonization - Laksmi, Dyah Ayu Vijaya (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
The distribution of inheritance in Islamic and civil law is based on different legal principles, often leading to disputes among heirs. Islamic law applies the faraid system, which mandates a fixed and predetermined division based on Sharia provisions. In contrast, civil law prioritizes testamentary freedom, allowing heirs to determine inheritance distribution according to their will. These differences significantly impact justice for heirs and the mechanisms for dispute resolution. This study employs a qualitative approach using a comparative method, analyzing Islamic legal texts, statutory regulations, and scholarly literature related to inheritance law. The findings indicate that Islamic inheritance law emphasizes family deliberation (musyawarah) as a primary dispute resolution mechanism, whereas civil law often relies on litigation through courts. Consequently, harmonization efforts are necessary to bridge these legal disparities. This can be achieved by strengthening the role of religious courts, implementing sharia-based mediation, and updating regulations concerning grants and wills. This study suggests that justice in inheritance distribution can be better ensured by integrating a more flexible and adaptive legal framework while also providing greater legal certainty for all heirs. These findings contribute to the ongoing discourse on legal pluralism and inheritance dispute resolution, emphasizing the need for a more integrative and balanced legal approach in Indonesia.